Hubungan Pengetahuan Ibu tentang Kesehatan Gigi dan Mulut dengan Kejadian Karies Gigi pada Anak Balita di Posyandu Wiratama - Nur Khamilatusy Sholekhah (Indonesian Journal of Dentistry, 2021)
Background: Dental health problems, especially dental caries, often occur in children. Parents' knowledge about the prevention of children's caries will greatly determine the dental health status of their children.Method: This study was an observational analytic study with a cross sectional approach. The study was conducted on 21 children aged 3 - 4 years at Posyandu Wiratama, Pudak Payung, Banyumanik, Semarang City, and their parents. Sample recruitment was carried out by total sampling. Dental and oral health of children was measured by the def-t index. Result: Based on the results of the analysis above, it is known that the significance value or Sig. (2-tailed) of 0.000, because the Sig. (2 tailed) 0.000 <less than 0.05, it means that there is a significant relationship between maternal education level variables and the severity of children's dental caries (deft-t). Conclusion: There is a relationship between mother’s knowledge about children's dental health and caries incidence of children aged 3-4 years at Posyandu Wiratama Semarang City.